Deteksi Logam Timbal (Pb) pada Ikan Nila (Oreochromis niloticus) di Sepanjang Sungai Kalimas Surabaya [Metal Detection Of Lead In Tilapia (Oreochromis niloticus) Along The Kalimas River In Surabaya] - Agustono Agustono; Jakfar Jakfar; Abdul Manan (Jurnal Ilmiah Perikanan dan Kelautan, 2014)
Abstract Industrial waste and urban waste containing heavy metals can pollute rivers and sea waters. Heavy metals can be divided into two parts, namely the essential and non essential, nonessential heavy metals can be toxic to both human beings and fish. Heavy metals that enter the water will have absorbed the deposition of the sediments and fish in one body of harmful heavymetals lead dalah. Based on the 2009 SNI maximum content of lead in fish is 0.3ppm. This study aims to know the lead content in tilapia, river water and sediment. The sampling process conducted in Surabaya Kalimas river. This study is descriptive, the results of lead content analysisconducted by the destructive method was then performed by using Atomic Absorption readings Spectrophotometer (AAS) with a wavelength of 283.3. Based on the analysis of lead content in Surabaya Kalimas river is not exceed the threshold value based on SNI.